Sony gets hacked - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case describes how in April and May of 2011 the hacktivist group Lulzec repeatedly broke through Sony's cyber security to hack the company, costing them millions of dollars and representing a new kind of Internet crisis.